Otthonom Tarnabod . My Own Private Taranbod - Hajdú, Eszter (Varjasi Farkas, Csaba, 2006)
Verzio FF Submission In the autumn of 2004 a unique programme to deal with homeless people was launched in Hungary. A small selected group of homeless families were given houses, gardens and animals in Tarnabod, a small village lying some 120 km from Budapest, in order to give them the chance to restart their lives. Who were these selected people? How would the poor people living in the village take to these "privileged" families? Would they accept or exclude the new arrivals? The film follows the personal dramas of three different families, while acquainting the viewer with the main participants of the programme and providing a glimpse into the life in this village.